2015
DOI: 10.1016/j.socscimed.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Social Trust's effect on suicide ideation between urban and non-urban areas: The Case of Japanese Adults in 2006

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…By contrast, emergency dispatches related to suicide attempts increased in 2020 compared with the previous two years. This increase could be partly explained by economic loss, 9,24,25 disrupted social networks 10 or reduced social capital, [26][27][28][29][30][31][32][33][34][35][36][37] and worsening of existing conditions including psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, emergency dispatches related to suicide attempts increased in 2020 compared with the previous two years. This increase could be partly explained by economic loss, 9,24,25 disrupted social networks 10 or reduced social capital, [26][27][28][29][30][31][32][33][34][35][36][37] and worsening of existing conditions including psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a cross-sectional study involving 10,094 older residents in Japan, mistrust and a lack of reciprocity at the individual level were associated with suicidal ideation even after controlling for psychological distress [19]. In another study among Japanese residents, individual-level social trust reduced the probability of suicidal ideation [23]. Precedent studies of the relationship between social capital and suicide were mainly conducted in neighborhood/community settings.…”
Section: Discussionmentioning
confidence: 99%
“…In residential or geographical areas, social capital has attracted attention for its protective effects against suicide. A growing number of studies have investigated the relationship between social capital and suicide-related factors [1423]. These studies demonstrated empirical support for a positive association between high social capital and a low suicide rate, less suicidal behavior, and decreased suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, Masayuki found individual-level mistrust was associated with suicidal ideation after adjusting for social support and psychological distress among the elderly living in the rural area [18]. The same result is also found that social trust accumulated reduce the probability that one will consider suicide among male living in urban areas and subjects with a mean age of 54.5 [19, 20]. In South Korea, by using a nationally representative longitudinal cohort database, Kim showed that the low interpersonal trust group has a greater likelihood of suicidal ideation [21].…”
Section: Introductionmentioning
confidence: 91%